Noise from the Writing Center - Boquet, Elizabeth H. (Utah State University, University Libraries, 2002)
In Noise from the Writing Center, Boquet develops a theory of ""noise"" and excess as an important element of difference between the pedagogy of writing centers and the academy in general. Addressing administrative issues, Boquet strains against the bean-counting anxiety that seems to drive so much of writing center administration. Pedagogically, she urges a more courageous practice, developed via metaphors of music and improvisation, and argues for ""noise,"" excess, and performance as uniquely appropriate to the education of writers and tutors in the center. Personal, even irreverent in style, Boquet is also theoretically sophisticated, and she draws from an eclectic range of work in academic and popular culture-from Foucault to Attali to Jimi Hendrix. She includes, as well, the voices of writing center tutors with whom she conducted research, and she finds some of her most inspiring moments in the words and work of those tutors. A provocative and path-breaking essay from one of the leading scholars in writing center theory and administration, Noise from the Writing Center is a must-read volume not only for writing center directors and tutors, but also for WPAs, department chairs, compositionists, and anyone with a stake in the role of writing centers in the post-secondary institution.